Diagnostics and Policy Advice for Supporting Roma Inclusion in Romania - World Bank (Washington, DC, 2014)
Romanian Roma families today constitute a large, young, and extremely poor ethnic minority group, facing exclusion from markets and services. Investments in Roma inclusion are essential for Romania to achieve its Europe 2020 social inclusion goals, and the considerable returns on such investments will lay a more solid foundation for achieving sustained, shared prosperity across Romanian society. Therefore, Roma inclusion is not only a moral imperative, but also smart economics for Romania. This report discusses what it will take for Romania to achieve the socioeconomic inclusion of its Roma population. The report identifies the most important socioeconomic achievement gaps of Romanian Roma. It identifies obstacles to Roma inclusion and examines the relevant institutional framework. It draws policy recommendations based on the observed gaps in outcomes and policies, informed by evidence on what works from international experience. These recommendations focus on providing support and enhancing opportunities for the next generation of Roma while helping to improve the living conditions of the current generation. In this context, the report is organized as follows: chapter one focuses on Roma inclusion is smart economics for Romania; chapter two presents socioeconomic achievement gaps of Roma; chapter three focuses on obstacles to Roma inclusion; and chapter four presents priority interventions and policy measures.